PROBLEMS OF DISTANCE EDUCATION - Shaytura, Sergey; Ordov, Konstantin; Pigoreva, Olga; Kosterina, Irina; Zyukin, Danil; Gerasimova, Vera (Revista Inclusiones, 2020)
The purpose of this paper is to identify problem areas in the field of distance education. These areas are educational content, the form in which the material is presented, the quality of distance education, the inclusion of distance education in full-time education programs, as well as the focus on the customer in education with a view to the student's employment. To identify the educational content of distance education portals, the authors have performed a comparative analysis of the most popular distance education sites. In the analysis, the authors have assessed the sites, focusing on a comparison of goals, the orientation of training, the attractiveness of design, and the ease of use. The quality of distance education is evaluated based on open statistical sources of the Ministry of Education and Science of the Russian Federation and the Pension Fund of Russia which collect information about graduates of Russian universities and verify them based on the personal insurance policy number. The authors also consider research data from the Higher School of Economics. The main results of the study include an analysis of successes in the development of distance education by large educational organizations, assessment of the quality of education based on statistical data on employment, and identification of trends and ways of using distance education in full-time education programs. The analysis presented in the paper can be used in organizing correspondence courses and distance education programs, as well as using distance learning methods in full-time education programs.